2003
DOI: 10.1002/bies.10413
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐strand disulphides in cell entry proteins: poised to act

Abstract: Cross-strand disulphides (CSDs) are unusual bonds that link adjacent strands in the same beta-sheet. Their peculiarity relates to the high potential energy stored in these bonds, both as torsional energy in the highly strained disulphide linkage and as deformation energy stored in the sheet itself. CSDs are relatively rare in protein structures but are conspicuous by their presence in proteins that are involved in cell entry. The finding that entry of botulinum neurotoxin and HIV into mammalian cells involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 51 publications
2
96
0
1
Order By: Relevance
“…To further characterize the rgp140 V3 intermonomer disulfide bond, we investigated its potential for PDI processing, and although we have not been able to assign an activity to the intersubunit disulfide bond, we have shown that it is potentially one of the disulfide bonds broken by PDI. This agrees with a hypothesis, based on the disulfide bonding pattern of gp120, that three disulfide bonds (spanning V1/V2, V3, and V4) are uncommon cross-strand disulfides (83). Such bonds are under stress and relatively unstable, making them prone to cleavage and release of their stored energy, which might drive conformational changes such as those involved in membrane fusion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To further characterize the rgp140 V3 intermonomer disulfide bond, we investigated its potential for PDI processing, and although we have not been able to assign an activity to the intersubunit disulfide bond, we have shown that it is potentially one of the disulfide bonds broken by PDI. This agrees with a hypothesis, based on the disulfide bonding pattern of gp120, that three disulfide bonds (spanning V1/V2, V3, and V4) are uncommon cross-strand disulfides (83). Such bonds are under stress and relatively unstable, making them prone to cleavage and release of their stored energy, which might drive conformational changes such as those involved in membrane fusion.…”
Section: Discussionsupporting
confidence: 91%
“…Such bonds are under stress and relatively unstable, making them prone to cleavage and release of their stored energy, which might drive conformational changes such as those involved in membrane fusion. With the V3 loop being involved in coreceptor binding, it was suggested that its disulfide bond would be the prime target for PDI processing (83).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not yet known how often a single disulfide bond in vivo will be exposed to the force levels we explored in this study, it does seem likely that the sensitivity of any particular thiol͞disulfide exchange reaction to a pulling force will depend very specifically on the environment surrounding the bond as well as the type of chemical reaction involved. For example, ⌬x r is likely to depend on a number of factors that also affect the rate of the thiol͞disulfide exchange reaction, including the temperature (41), type of reducing agent (42), pH (42), electrostatics (43), the reaction mechanism (28), and the torsional strain present in the protein structure (21,44,45). Any combination of these effects that cause ⌬x r to be Ͼ1 Å would lead to a near 2-fold increase in reduction rate over just 20 pN of applied force, suggesting that force-catalyzed disulfide reduction may play an important role in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…A feature of ϪRHStaple bonds is the close proximity of the ␣-carbon atoms of the 2 cysteine residues that can impart strain on the bond. 27,30 The distance between the ␣-carbons of the Cys3-Cys5 bond is 4.01 Å (Table 2, average of the 2 structures), compared with a mean of 5.62 Å for all disulfides in a nonredundant set of X-ray structures. 31 The crossveinless 2 and procollagen 2A C domain structures were used to predict the structure of the VWF C2 domain using the I-TASSER protein structure prediction tool.…”
Section: Predicted Structure Of the C2 Domain Of Vwfmentioning
confidence: 99%